2014
DOI: 10.1371/journal.pone.0108775
|View full text |Cite
|
Sign up to set email alerts
|

The Mycotoxin Deoxynivalenol Predisposes for the Development of Clostridium perfringens-Induced Necrotic Enteritis in Broiler Chickens

Abstract: Both mycotoxin contamination of feed and Clostridium perfringens-induced necrotic enteritis have an increasing global economic impact on poultry production. Especially the Fusarium mycotoxin deoxynivalenol (DON) is a common feed contaminant. This study aimed at examining the predisposing effect of DON on the development of necrotic enteritis in broiler chickens. An experimental Clostridium perfringens infection study revealed that DON, at a contamination level of 3,000 to 4,000 µg/kg feed, increased the percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(84 citation statements)
references
References 41 publications
2
80
0
2
Order By: Relevance
“…There have been contradictory reports on the effect of DON on the CP digestibility. Dänicke et al (Maresca et al, 2002;Kolf-Clauw et al, 2009;Antonissen et al, 2014). It was also reported that DON may decrease the expression of tight junction protein such as claudin-4 (Pinton et al, 2010) as well as cause the inhibition of the regeneration of damaged intestinal epithelial cells (Ueno, 1985;Hussein and Brasel, 2001).…”
Section: Effect Of Deoxynivalenol On Apparent Ileal Digestibilitymentioning
confidence: 99%
“…There have been contradictory reports on the effect of DON on the CP digestibility. Dänicke et al (Maresca et al, 2002;Kolf-Clauw et al, 2009;Antonissen et al, 2014). It was also reported that DON may decrease the expression of tight junction protein such as claudin-4 (Pinton et al, 2010) as well as cause the inhibition of the regeneration of damaged intestinal epithelial cells (Ueno, 1985;Hussein and Brasel, 2001).…”
Section: Effect Of Deoxynivalenol On Apparent Ileal Digestibilitymentioning
confidence: 99%
“…A number of these factors have been tested and confirmed under controlled experimental conditions. These include high stocking density (Tsiouris et al, 2015), presence of moderately high concentrations of deoxynivalenol in the feed (Antonissen et al, 2014) and coccidiosis (Williams, 2005). Surprisingly, chronic heat stress tends to protect the birds from necrotic enteritis (Calefi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As DON is known to alter the intestinal barrier [14, 15, 17], an impact of DON on disease susceptibility could be assumed. However, the exact outcome of co-exposure to Fusarium mycotoxins and Salmonella infection is difficult to predict, and can be influenced by the animal host species, the bacterial strain and the effect of the mycotoxin on the bacterium, the host cells and the host-pathogen interaction.…”
Section: Discussionmentioning
confidence: 99%
“…DON negatively affects the intestinal barrier in many species by its impact on cell viability and proliferation, intestinal morphology, intestinal mucus layer, production of antimicrobial peptides, epithelial integrity, and modulation of digestive and absorptive processes [1417]. Hence, this can lead to an enhanced susceptibility to enteric diseases, such as necrotic enteritis in broiler chickens [15, 18]. …”
Section: Introductionmentioning
confidence: 99%